Participatory Varietal Selection, Participatory Plant Breeding, and Varietal Change - Walker, Thomas S. (World Bank, Washington, DC, 2012)
Participatory varietal selection (PVS) and participatory plant breeding (PPB) are relatively new terms that encompass both old and new concepts and procedures. The difference between PVS and PPB hinges on the degree and timing of farmer involvement in plant breeding. To illustrate the essential features of PVS and PPB, this study draws on an example of varietal change in Peru. In the mid-1980s, potato breeders in Peru and the International Potato Program (CIP) jointly decided to evaluate advanced clonal material from a diverse late-blight resistant population in farmers' fields. In return for their support, farmers received one-half of the output of the trials. By the time Canchan-INIAA variety was released, dozens of farmers were growing it, and a considerable amount of seed had been distributed via the informal seed system.